Stakeholder collaboration based on an innovated tourism product club model - an empirical investigation of the Parenzana product club. (4th November 2019) - Ribarić, Robert; Stipanović, Christian
The aim of this study is to analyse the potential of a tourism product club, as a form of collaboration, in the development of a tourism product. The study applies a qualitative approach and consists of a theoretical part and an applicative part. Structured interviewing in the field was used to survey 49 respondents and the data were processed using thematic coding and qualitative content analysis. The theoretical part includes a schematic diagram of a tourist product club model that would ensure the competitiveness of an integrated tourism product, drive entrepreneurship and encourage the entrepreneurial activities of stakeholders. The applicative part investigates the possibilities of valorising, for the purposes of tourism, the Parenzana route, which passes through two countries, Croatia and Slovenia. Based on the current state, fundamental objectives are defined that could be accomplished through the synergy of innovated operational strategies, resulting in a highly-developed, integrated tourism product based on the Parenzana product club model.